Understanding COVID-19 booster information seeking in a collectivist context: the roles of social expectations, trust in experts, and uncertainty - Li, Xiaoshan Austin; Hubbard, Katharine; Hwang, Jooyun (Frontiers in Public Health, 2025)
BackgroundEffective public health communication relies on understanding how individuals seek information during health emergencies. While previous work has investigated vaccine hesitancy and acceptance, little is known regarding the psychological and social motivations behind COVID-19 booster information-seeking in collectivist societies.ObjectiveThis study extends the Risk Information Seeking and Processing (RISP) model to explore the impact of trust in experts, risk uncertainty, and subjective informational norms on the public’s intention to seek information regarding COVID-19 booster shots in China.MethodsA national survey of 616 adults in China was undertaken. Structural equation modeling (SEM) examined hypothesized relationships among perceived advantages and disadvantages, affective responses, lack of information, trust in the expertise of others, uncertainty, perceived control over behavior, and social norms.ResultsInformational subjective norms were the most significant predictor of intentions to seek information, indicating the influence of collectivist expectations on individual action. Trust in experts was positively associated with perceived risks and inversely related to perceived benefits—and decreased perceived information insufficiency. Uncertainty increased individuals’ perceived ability to gather and interpret information, but affective responses had limited direct effects.ConclusionFindings highlight the need to incorporate social norms, trust relationships, and uncertainty management into public health education campaigns to support vaccine promotion. This study offers empirical evidence for designing culturally adaptive communication interventions that promote booster uptake among collectivist societies and comparable environments.